Economic management instrument for enhanced supply of utilities to megacities. (March 2019) - Stenis, Jan; Hogland, William; Sokolov, Michael; Rud, Vasily; Davydov, Roman
Abstract: A cost structure is proposed to enhance the supply of utilities to megacities on a regional operating scale. The introduced methodology involves business administration theory and economics and employs the previously introduced equality principle and the EUROPE (Efficient Use of Resources for Optimal Production Economy) model to impose shadow costs on supply losses to induce economic incentives to improve the functionality of megacities. A case study presents the practical application in an Asian context. It is concluded that the introduced methodology makes the megacities more efficient and improve their functionality. Profitability increases, the technology is advanced, and the environment improves when the EUROPE model is applied on activities that involve supply flows at higher policy analysis levels. Application of an introduced key factor encapsulates megacity aspects. The equity of the regional access to facilities is improved. The developed methods support decision-making when managing megacity supply.